Imām, jang va shahādat - Khomeini, Ruhollah (Intishārāt-i Yāsir bū bankārī-i Vizārat-i Irshād-i Islāmī Kull-i Tablīghāt va Intisharat, 1983)
On holy war and martydom; excerpts from the speeches of the founder of the 1979, Islamic revolution in Iran.